Correlation of Leucine Intake with Serum Prolactin and Breast Milk Protein Levels in Breastfeeding Women - Lestari, Ni Putu Yunita Sri; Wardani, Widya Kusuma; Ratnawati, Linda; Nurseta, Tatit; Rahardjo, Bambang (Green Publisher Indonesia, 2022)
Breast milk is the best choice food for a baby’s growth and development of infants at some point of the primary 6 months of life. Fulfillment of nutrition during breastfeeding is an important requirement, one of which is the intake of the amino acid leucine which is said to affect prolactin as a regulator of breast milk production and protein synthesis in breast milk. This can support the quality and quantity of breast milk to meet the nutritional needs of infants support infant growth and development and reduce the incidence of stunting at the age of toddlers. This research aims to determine the relationship between leucine intake and levels of prolactin and protein in breast milk in breastfeeding mothers. This research is an analytic observational study with a cross-sectional method. This study carried out normality using the Kolmogorov-Smirnov test and using the Pearson correlation test to determine the relationship between variables. Based on the test results of the relationship between leucine intake and serum prolactin levels, a significance value of 0.005 (p<0.05) was obtained with a correlation coefficient value of 0.183 and the relationship between leucine intake and breast milk protein levels obtained a significance value of 0.033 (p<0.05) with a correlation coefficient of 0.147. The results of this test showed a significant relationship between these variables. There is a weak correlation between leucine intake and levels of prolactin and protein in breast milk